Pentingnya Penginjilan dalam Pertumbuhan Gereja - Yohanes Joko Saptono (DIEGESIS: Jurnal Teologi Kharismatika, 2019)
Evangelism is one of the key factors of church growth. A church’s recognition of the importance of evangelization always brings about an impact on the growth of a church; to its life and works. Accordingly, churches who recognize evangelization as crucial to their growth would consequently transform it into their personal, communal, and institutional priorities: Evangelization would be addressed seriously; all resources would be directed towards it; and all approaches, strategies, methods, and various types and scope of techniques would be employed to draw people to Christ. It was evident that any motivation and even the faintest competence can be used by God to bring many people to Christ, as long as they are directed to glorify the name of God. Furthermore, as a result of evangelization, the biological growth of churches occurs, either through relocation of church members or due to the conversion of souls at all times and places. In the same manner, churches grow in quality, quantity, in its complexities of evangelization, and are continuously renewed by the gospel, as well as experiencing unceasing growth. Evangelism is indeed the key feature of a church’s growth. Likewise, from the historical-theological perspective, evangelism also has a great impact on the growth of the church. The ups and downs of evangelism carried out by the church have therefore been an indicator of the church’s growth. The paper finally argues that without evangelization, the growth of a church will not transpire, and ultimately, churches who grow are churches who evangelize.AbstrakPenginjilan merupakan salah satu faktor penentu pertumbuhan gereja. Kesadaran akan hal ini membuat gereja memahami perlunya penginjilan dalam segala aspek kehidupan dan karyanya.  Sehingga penginjilan menjadi prioritasnya baik secara personal, komunal maupun institusional.  Penginjilan akan ditangani dengan sangat serius. Segala sumber daya yang dimiliki akan diarahkan untuk penginjilan. Mereka akan menggunakan berbagai macam pendekatan, strategi, metode dan tehnik penginjilan dengan aneka ragam bentuk dan ruang lingkupnya.  Motivasi apapun dan kompetensi yang lemah sekalipun, bisa dipakai Tuhan untuk membawa banyak orang kepada Kristus. Pertumbuhan gereja secara biologis atau karena perpindahan anggota gereja atau karena pertobatan jiwa-jiwa baru terjadi pada segala waktu dan tempat.  Pertumbuhan gereja secara kualitas, kuantitas maupun kompleksitas organisasinya merupakan hasil dari penginjilan yang dilakukannya. Gereja senantiasa diperbaharui oleh Injil dan oleh karenanya gereja senantiasa mengalami pertumbuhan.Penginjilan adalah kunci pertumbuhan gereja.  Dalam perspektif historis-teologis, penginjilan mempunyai pengaruh yang besar bagi pertumbuhan gereja. Oleh karena itu, tinggi rendahnya penginjilan yang dilakukan gereja selalu menjadi indikator bertumbuh tidaknya gereja. Sebab penginjilan akan mendorong pertumbuhan gereja. Sedangkan gereja yang bertumbuh tentu akan melakukan penginjilan.